Creating an Indonesian Archipelago Creation Dance for Elementary School-Aged Children - Mikaresti, Pamela; Mansyur, Herlinda (International Conference on Elementary Education, 2022)
Preserving traditional dances of the Indonesian archipelago, one of which is through education starting from elementary school-aged children. However, there are some obstacles faced by teachers of elementary schools, including the lack of knowledge of art because the learning material obtained at colleges is not adequate. In addition, art teachers who are classroom teachers at elementary schools generally do not have artistic skills, especially in terms of dance. The purpose of this study is to create an Indonesian archipelago creation dance for elementary school-aged children as a step in inheriting cultures through introducing the cultures of the Indonesian archipelago to elementary school-aged children. In terms of research method, this study used ethnographic qualitative research method and dance creation method. The result of this study is a creation dance resulting from the development of the traditional dances of Andun Dance and Kejei Dance from Bengkulu. In conclusion, this Indonesian archipelago creation dance is an innovation in introducing the regional cultures of the Indonesian archipelago by including this learning material in the course of Art Education at Elementary School in the study program of Elementary School Teacher Education.